Cardiovascular responses to hydrogen peroxide into the nucleus tractus solitarius - Cardoso, Leonardo Maximo; de Almeida Colombari, Debora Simoes [UNESP]; Menani, José Vanderlei [UNESP]; Toney, Glenn M.; Chianca, Deoclecio Alves; Colombari, Eduardo [UNESP] (Amer Physiological Soc, 2009)
Cardoso LM, Colombari DSA, Menani JV, Toney GM, Chianca Jr. DA, Colombari E. Cardiovascular responses to hydrogen peroxide into the nucleus tractus solitarius. Am J Physiol Regul Integr Comp Physiol 297: R462-R469, 2009. First published June 10, 2009; doi:10.1152/ajpregu.90796.2008.-The nucleus tractus solitarius (NTS), a major hindbrain area involved in cardiovascular regulation, receives primary afferent fibers from peripheral baroreceptors and chemoreceptors. Hydrogen peroxide (H(2)O(2)) is a relatively stable and diffusible reactive oxygen species (ROS), which acting centrally, may affect neural mechanisms. In the present study, we investigated effects of H(2)O(2) alone or combined with the glutamatergic antagonist kynurenate into the NTS on mean arterial pressure (MAP) and heart rate (HR). Conscious or anesthetized (urethane and alpha-chloralose) male Holtzman rats (280-320 g) were used. Injections of H(2)O(2) (125 to 1500 pmol/40 nl) into the intermediate NTS of anesthetized rats evoked dose-dependent and transient hypotension (-18 +/- 3 to -55 +/- 11 mmHg) and bradycardia (-16 +/- 5 to -116 +/- 40 bpm). Injection of the catalase inhibitor 3-amino-1,2,4-triazole (100 nmol/40 nl) into the NTS also produced hypotension and bradycardia. Previous injection of the ionotropic L-glutamate receptor antagonist kynurenate (7 nmol/40 nl) attenuated by 48% the bradycardic response, without changing the hypotension evoked by H(2)O(2) (500 pmol/40 nl) in anesthetized rats. The antioxidant L-ascorbate (600 pmol/80 nl) injected into the NTS attenuated the bradycardic (42%) and hypotensive (67%) responses to H(2)O(2) (500 pmol/40 nl) into the NTS. In conscious rats, injection of H(2)O(2) (50 nmol/100 nl) into the NTS also evoked intense bradycardia (-207 +/- 8 bpm) and hypotension (-54 +/- 6 mmHg) that were abolished by prior injection of kynurenate (7 nmol/100 nl). The results show that H(2)O(2) into the NTS induces hypotension and bradycardia probably due to activation of glutamatergic mechanisms.
Keywords: reactive oxygen species; catalase inhibition; kynurenic acid; blood pressure; heart rate